2014
DOI: 10.1016/j.envres.2014.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers of mercury-induced autoimmune dysfunction: A cross-sectional study in Amazonian Brazil

Abstract: Mercury is an ubiquitous environmental contaminant, causing both neurotoxicity and immunotoxicity. Given its ability to amalgamate gold, mercury is frequently used in small-scale artisanal gold mining. We have previously reported that elevated serum titers of antinuclear autoantibodies (ANA) are associated with mercury exposures of miners in gold mining. The goal of this project was to identify novel serum biomarkers of mercury-induced immunotoxicity and autoimmune dysregulation. We conducted an analysis of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 29 publications
0
22
1
Order By: Relevance
“…Mercury is a widely distributed environmental and industrial pollutant (42) that in both humans and animals, induces a milder form of autoimmunity including autoAbs and membranous nephropathy (4346). The characteristics of mercury-induced autoimmunity (HgIA) are similar to SLE and include lymphocyte proliferation, increased class II MHC expression, hypergammaglobulinemia, polyclonal Abs to self-antigens, notably anti-nuclear Abs (ANAs), and to some extent immune complex deposits in mice (47), as well as necrotizing vasculitis in rats (48–52).…”
Section: Introductionmentioning
confidence: 99%
“…Mercury is a widely distributed environmental and industrial pollutant (42) that in both humans and animals, induces a milder form of autoimmunity including autoAbs and membranous nephropathy (4346). The characteristics of mercury-induced autoimmunity (HgIA) are similar to SLE and include lymphocyte proliferation, increased class II MHC expression, hypergammaglobulinemia, polyclonal Abs to self-antigens, notably anti-nuclear Abs (ANAs), and to some extent immune complex deposits in mice (47), as well as necrotizing vasculitis in rats (48–52).…”
Section: Introductionmentioning
confidence: 99%
“…19 In rabbit and rat models, exposure to Hg 0 causes autoimmune disease, similar to the immune cell activity observed in patients with MS. 20, 21 Investigators in studies of Amazonian gold miners have reported associations of low-level urinary Hg 0 concentrations (3.7 mg/L) with both elevated cytokines and antinuclear antibodies, which are biomarkers associated with immune response and autoimmune disease, respectively. [22][23][24] Tremor is an involuntary movement characterized by oscillatory motion, occurring during rest or activity. The prevalence of tremor in people with MS ranges from 25% to 60%, [25][26][27] and this tremor is characterized by demyelinating lesions in the brain that produce intention tremor, the most common type of cerebellar tremor.…”
mentioning
confidence: 99%
“…However, among these metals, exposure to mercury is most closely associated with elevated risk of multiple autoimmune conditions as an outcome of immunotoxicity [48]. It also promotes inflammatory disease via induction of both the ecyclooxygenase-2 and inducible nitric oxide synthase genes [49].…”
Section: Mercurymentioning
confidence: 99%